2016
DOI: 10.1093/pan/mpw026
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Emotion on Trust

Abstract: Political scientists frequently wish to test hypotheses about the effects of specific emotions on political behavior. However, commonly used experimental manipulations tend to have collateral effects on emotions other than the targeted emotion, making it difficult to ascribe outcomes to any single emotion. In this letter, we propose to address this problem using causal mediation analysis. We illustrate this approach using an experiment examining the effect of emotion on dyadic trust, as measured by the trust g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 27 publications
2
40
0
1
Order By: Relevance
“…The research design in this article addresses these two threats to identification by randomly assigning participants to a procedure that induces a mild state of fear during the course of an interview. I use a common emotion induction from experimental psychology in which participants are asked to recall in detail a situation that has made them feel a targeted emotion (Strack, Schwarz and Gschneidinger, 1985;Lerner and Keltner, 2001;Myers and Tingley, 2016). To deal with the first threat to identification, I randomly assign participants into the fear treatment so that the treatment is orthogonal to any individual characteristics.…”
Section: Research Design: Identifying the Effect Of Fearmentioning
confidence: 99%
“…The research design in this article addresses these two threats to identification by randomly assigning participants to a procedure that induces a mild state of fear during the course of an interview. I use a common emotion induction from experimental psychology in which participants are asked to recall in detail a situation that has made them feel a targeted emotion (Strack, Schwarz and Gschneidinger, 1985;Lerner and Keltner, 2001;Myers and Tingley, 2016). To deal with the first threat to identification, I randomly assign participants into the fear treatment so that the treatment is orthogonal to any individual characteristics.…”
Section: Research Design: Identifying the Effect Of Fearmentioning
confidence: 99%
“…Not to mention, a number of researchers have put emotions as an important consideration in understanding the development of trust and its changes, for example, Williams [16] and Andersen and Kumar [17] suggested that emotions influence how people judge on others' trust, Tomlinson and Mayer [18] agreed that emotions have impact on trust repair, and a study showed that people experiencing positive valence (i.e. happy and gratitude) are more receptive to increase their trust level [6]. This could somehow summarize that expectation that we expect upon interaction is constitute by positive or negative feeling that we felt which lead to judgment or decision-making about something or someone.…”
Section: Background Studymentioning
confidence: 99%
“…Since trust is one of the key elements in the process of persuasion [1], one need to be persuaded repetitively in repetitive interactions which will only possible to happen if users trust the systems. Since [6] have discovered that emotion has influence on trust, we expect that its effect on persuasion using persuasive technology would be positively mediated.…”
Section: H1: Emotion Will Positively Affect Trust In Persuasive Technmentioning
confidence: 99%
See 1 more Smart Citation
“…21. On the difficulty of disentangling specific emotions, see Myers and Tingley 2016. in imputing emotions to others, incentives to misrepresent, etc. ), it is far more difficult to argue that this caused any particular event to occur.…”
Section: Emotions In Conflict Decision Makingmentioning
confidence: 99%